Ubiquitination Destabilizes Protein Sphingosine Kinase 2 to Regulate Glioma Malignancy - Wang, Hongliang; Zhao, Bing; Bian, Erbao; Zong, Gang; He, Jie; Wang, Yuyang; Ma, Chunchun; Wan, Jinghai (Frontiers in Cellular Neuroscience, 2021)
Gliomas are the most common and lethal malignant tumor in the central nervous system. Tumor oncogene Sphingosine Kinase2 (SphK2) was previously found to be up-regulated in glioma tissues and enhance glioma cell epithelial-to-mesenchymal transition through AKT/β-catenin pathway. Nevertheless, ubiquitination of SphK2 protein has yet to be well elucidated. In this study, mass spectrometry analysis was performed to identify the proteins interacted with SphK2 protein. Co-immunoprecipitation (Co-IP) and Immunoblotting (IB) was used to prove the specific interaction between SphK2 protein and the Neural Precursor Cell Expressed, Developmentally Down-Regulated 4-Like (NEDD4L) protein. Fluorescence microscopy was used for detecting the distribution of related proteins. Ubiquitylation assay was utilized to characterize that SphK2 was ubiquitylated by NEDD4L. Cell viability assay, flow cytometry assay and transwell invasion assay were performed to illustrate roles of NEDD4L mediated SphK2 ubiquitination in glioma viability, apoptosis, invasion, respectively. We found that NEDD4L directly interacted with SphK2 and ubiquinated it for degradation. Ubiquitination of SphK2 mediated by NEDD4L overexpression suppressed glioma cell viability and invasion, but promoted glioma apoptosis. Knockdown of NEDD4L presented opposite results. Moreover, further results suggested that ubiquitination of SphK2 regulated glioma malignancy via AKT/β-catenin pathway. In vivo assay also supported above findings. This study reveals that NEDD4L mediates SphK2 ubiquitination to regulate glioma malignancy and may provide some meaningful suggestions for glioma treatment.